Should UI Benefits Really Fall over Time? - John Hassler; José V. Rodriguez Mora (Center for Economic Studies and ifo Institute (CESifo), 2002)
The issue of whether unemployment benefits should increase or decrease over the unemployment spell is analyzed in an analytically tractable model allowing moral hazard, adverse selection and hidden savings. Analytical results show that when the search productivity of unemployed is constant over the unemployment spell, benefits should typically increase or be constant. The only exception is when there is moral hazard and no hidden savings. In general, adverse selection problems calls for increasing benefits, moral hazard problems for constant benefits and decreasing search productivity for decreasing benefits.
Keywords: 330; unemployment benefits; search; moral hazard; adverse selection